2022
DOI: 10.1007/s12144-022-03941-y
|View full text |Cite
|
Sign up to set email alerts
|

School and learning contexts during the COVID-19 pandemic: Implications for child and youth mental health

Abstract: Despite significant disruption to school during the COVID-19 pandemic, research on the impact on children is sparse. This study examines in-person and virtual learning contexts and the impact of school format on mental health (MH). Children and adolescents were recruited from community and clinical settings. Parents and children completed prospective online surveys about school experiences (November 2020) and MH symptoms (February/March 2021), including school format and activities. Standardized measures of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…In a meta-analysis of 51 studies (67,378 youth), Allen and colleagues 14 identified several factors that foster connectedness at school and suggested that such efforts to address school connectedness would support students' well-being. Even when schools were open to in-person learning, recent research illustrated low levels of social-learning activities (e.g., group work, 1:1 teacher-student time), 4 which could explain lower levels of connectedness during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a meta-analysis of 51 studies (67,378 youth), Allen and colleagues 14 identified several factors that foster connectedness at school and suggested that such efforts to address school connectedness would support students' well-being. Even when schools were open to in-person learning, recent research illustrated low levels of social-learning activities (e.g., group work, 1:1 teacher-student time), 4 which could explain lower levels of connectedness during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…School Changes: Ease of Adapting Children's learning environments during the pandemic are much different than before the pandemic, 4 and differences in the mode of school instruction may be important for their MH. 4,6 Stable learning environments that involve structured routines support behavior and achievement 35 ; however, schools have experienced repeated closures and reopenings and have had to implement several public health measures, all of which have the potential to erode the structure and stability of the learning environment. 8 Our results showed that greater difficulty adapting to changes at school was associated with greater MH symptoms.…”
Section: School Connectednessmentioning
confidence: 99%
See 3 more Smart Citations